Assessment of different in vitro sperm challenges and in vivo fertility of bovine semen batches - Oliveira, Letícia Zoccolaro; Ribeiro, Lucas Bernardes; Silva, Luiz Gustavo Teodoro da; Oliveira, Clara Slade; Dias, Erika Aline Ribeiro; Campanholi, Suzane Peres; Campos, Carla Cristian; Oliveira, Maiana Visoná de; Monteiro, Fabio Morato (Brazilian Journal of Veterinary Research and Animal Science, 2017)
The aim of this work was to submit sperm cells to different laboratory challenges and to compare in vitro results with in vivo semen fertility. Four different batches from the same Brangus bull were used in a timed-AI program of 332 Brangus cows. Each batch (B) was submitted to the following procedure: semen sample was thawed at 36°C for 30 seconds (control). Sperm motility parameters, plasma membrane integrity, sperm morphology, and concentration were assessed. Then, an aliquot of thawed sample was incubated in a water bath at 45°C for 40 min (thermal challenge group; TCG) and another aliquot was centrifuged at 500 xg (Percoll gradient 45%/90%) for 15 min (centrifugation challenge group; CCG). Centrifuged semen was also submitted to another thermal challenge, being incubated (water bath) at 45°C for 40 min (centrifugation + thermal challenge group; CTCG). At the end of each challenge (CCG, TCG, and CTCG), the same laboratory tests used for control group were repeated. The following conception rates (CR) were observed for each batch: B1 = 48.9% (44/90); B2 = 44.2% (23/52); B3 = 55.5% (40/72); B4 = 43.2% (51/118); (p < 0.10). In the lab, B3 presented higher (p ≤ 0.05) progressive motility (PM) than B4 after thawing (control group) and after all sperm challenges (TCG, CCG, and CTCG). However, despite B3 and B4 having demonstrated a similar percentage of plasma membrane integrity (PMI) to the control group (B3 = 66.7 ± 1.3 and B4 = 65.2 ± 3.3), B3 demonstrated higher (P ≤ 0.05) percentage of PMI (37.2 ± 2.5) than B4 (26.7 ± 3.3) after passing through the most stressing in vitro challenge (CTCG). The semen batch presenting the highest resistance to in vitro challenges was the one that presented a trend for higher in vivo fertility, suggesting that submitting semen samples to laboratory challenges may be an interesting alternative for selecting batches with greater field fertility.